2017
DOI: 10.1016/j.ajpath.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Oral Corticosterone Administration Reduces Insulitis but Promotes Insulin Resistance and Hyperglycemia in Male Nonobese Diabetic Mice

Abstract: Steroid-induced diabetes is the most common form of drug-induced hyperglycemia. Therefore, metabolic and immunological alterations associated with chronic oral corticosterone were investigated using male nonobese diabetic mice. Three weeks after corticosterone delivery, there was reduced sensitivity to insulin action measured by insulin tolerance test. Body composition measurements revealed increased fat mass and decreased lean mass. Overt hyperglycemia (>250 mg/dL) manifested 6 weeks after the start of glucoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 63 publications
(45 reference statements)
4
30
1
Order By: Relevance
“…Excess adiposity, such is seen in obesity, has been associated with increased insulin resistance. Previous work from our lab shows increased fat mass following 12 weeks of dexamethasone treatment (Hochberg et al 2015) in lean mice, in accordance with what others have reported (Burke et al 2017), as well as reduced insulin sensitivity. However, to our surprise, the glucocorticoid treatment in obese mice led to a lipodystrophic phenotype, which indicates the disturbances in glucose homeostasis are not a result of increased fat mass.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Excess adiposity, such is seen in obesity, has been associated with increased insulin resistance. Previous work from our lab shows increased fat mass following 12 weeks of dexamethasone treatment (Hochberg et al 2015) in lean mice, in accordance with what others have reported (Burke et al 2017), as well as reduced insulin sensitivity. However, to our surprise, the glucocorticoid treatment in obese mice led to a lipodystrophic phenotype, which indicates the disturbances in glucose homeostasis are not a result of increased fat mass.…”
Section: Discussionsupporting
confidence: 92%
“…There is some debate as to which genes glucocorticoids are acting on to promote lipolysis. Downregulation of Pde3b (Xu et al 2009) and upregulation of β-adrenergic receptors (Lacasa et al 1988) and ATGL transcripts (Campbell et al 2011;Serr et al 2011;Shen et al 2017) have been proposed as possible mechanisms. We found ATGL, the rate limiting enzyme for adipose triglyceride lipolysis, to be synergistically activated by obesity and glucocorticoid-treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were fasted for 2 h and were injected intraperitoneally with 0.75 units/kg Humulin R insulin as previously described [ 19 ]. Islet histology procedures have been described [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Mice were fasted for 2 h and were injected intraperitoneally with 0.75 units/kg Humulin R insulin as previously described [ 19 ]. Islet histology procedures have been described [ 19 , 20 ]. Briefly, the antibodies used were as follows: insulin (Invitrogen; 18-0067; used at 1 : 800), glucagon (Cell Signaling Technologies; 8233; used at 1 : 400), Aldh1a3 (Novus Biologicals; NBP2-15339; used at 1 : 100), and Nkx6.1 (F55A12; 1 : 200; [ 21 ]).…”
Section: Methodsmentioning
confidence: 99%
“…For creating a male mouse model of Cushing's syndrome, when those mice became eight-week-old, drinking water was replaced with a 1% ethanol solution containing 100 μg/mL corticosterone (Wako Pure Chemical Industries) or a vehicle, and those mice were remained to be fed and watered ad libitum as previously reported [10][11][12]. After 4-wk corticosterone treatment, mice were anesthetized with intraperitoneal injection of sodium pentobarbital (Kyoritsu Seiyaku) at 75 mg/kg body weight and sacrificed.…”
Section: Mice and Glucocorticoid Treatmentmentioning
confidence: 99%